2000
DOI: 10.1016/s0045-7825(99)00102-4
|View full text |Cite
|
Sign up to set email alerts
|

On a parabolic quadrilateral finite element for compressible flows

Abstract: We present a 9-node ®nite element for compressible¯ow solutions. A high-order derivative upwind term and a shock capturing term are employed for stability and accuracy of the formulation. We give the solutions of various example problems to illustrate our experiences with the element. Ó

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…7. It can be observed that the solution obtained with the initial mesh is close to the results obtained by Hendriana and Bathe (2000) with reference to the position of the shock wave as well as its intensity. Results obtained by Le Beau et al (1993) are not shown in Fig.…”
Section: Supersonic Flow Over a Bumpsupporting
confidence: 70%
“…7. It can be observed that the solution obtained with the initial mesh is close to the results obtained by Hendriana and Bathe (2000) with reference to the position of the shock wave as well as its intensity. Results obtained by Le Beau et al (1993) are not shown in Fig.…”
Section: Supersonic Flow Over a Bumpsupporting
confidence: 70%
“…This technique involves adding a higher order derivative artificial diffusion term to the Galerkin formulation for greater accuracy and stability [4],…”
Section: Higher Order Derivative Artificial Diffusion Methodsmentioning
confidence: 99%
“…The pure Galerkin formulation is realized in the limit of very fine discretization. In references [4,7,13] the factor C ¼ 1 9 was used for the one-dimensional FEM, derived analytically. The calculation of C for the MFS is more involved and is presented in Appendix A.…”
Section: Higher Order Derivative Artificial Diffusion Methodsmentioning
confidence: 99%
See 2 more Smart Citations